Understanding and building clean(er) sport together: Community-based participatory research with elite athletes and anti-doping organisations from five European countries. (July 2021) - Petróczi, Andrea; Heyes, Andrew; Thrower, Sam N.; Martinelli, Laura A.; Backhouse, Susan H.; Boardley, Ian D.; ,
Abstract: Background: In sport the narrative is changing from anti-doping to pro-clean sport. Yet, our understanding of what 'clean sport' means to athletes is notably absent from the literature. Objectives: Working together with elite athletes and National Anti-Doping Organisations (NADOs), this study explored the meaning and importance of 'clean sport' and 'clean athlete identity'. Design: Community-based participatory research design was employed to explore (a) how elite athletes define clean sport and being a clean athlete; (b) the hopes and challenges associated with clean sport and being a clean athlete; and (c) what can be done in anti-doping to elicit clean sport. Methods: Five elite athletes in five European countries (Germany, Ireland, Netherlands, Slovenia and United Kingdom) were recruited as co-researchers by their respective NADOs, trained for their role as co-researchers and individually interviewed. Seventy-seven elite athletes were then purposefully recruited for 12 athlete-led national focus groups. Finally, the five athlete co-researchers and five athlete participants took part in one 2.5-h long international focus group. Results: Reflexive thematic analysis resulted in generating four overarching themes: 'clean is being true to the self', 'clean performance enhancement has multiple meanings', 'clean is not a solo act' and 'the problems and solutions are systemic'. Collectively, the themes showed that the clean athlete identity is generally rooted in upbringing, early experiences and love of sport; and characterised by continued, intrinsically motivated commitment to fundamental values and morals acquired in childhood. In contrast, the concept of clean performance-enhancement is highly idiosyncratic and flexible. Elite athletes value anti-doping efforts but their experiences of disparity and unfairness in doping control undermine their trust in anti-doping. Conclusion: Clean athlete identity is a social endeavour and artefact, which needs to be reflected in and developed through evidence-informed anti-doping interventions. Raising athletes' voices via collaboration and participatory research can be an enriching experience for athletes and researchers alike, and a worthwhile endeavour for sport organisations with responsibility for anti-doping. To make anti-doping education personally relevant, the richness of individual interpretation of 'clean' for the self (i.e., clean athlete identity) and performance-enhancement must be acknowledged, respected and cultivated. Graphical abstract: Image 1 Highlights: Clean athlete identity is rooted in upbringing, early experiences and love of sport. Definition of clean performance enhancement is highly idiosyncratic. Clean athlete identity is reinforced, but not created, by values-based education. Disbelief and scepticism that 'clean sport' could be achieved was evident. Problems of anti-doping were identified as systemic, thus solutions must also be systemic.